Convenient synthesis of some new pyrazolo[5,1-c]triazines, isoxazolo[3,4-d] pyrimidine and pyridine derivatives containing benzofuran moiety - Abdelhamid, Abdou Osman; Fahmi, Abdelgawad Ali; Alsheflo, Amna Ali Mohamed (European Journal of Chemistry, 2012)
Pyrazolo[5,1-c][1,2,4]triazine, [1,2,4]triazolo[3,4-c][1,2,4]triazine, benzo[4,5]-imidazo[2,1-c][1,2,4]triazine, isoxazole, isoxazolo[3,4-d]pyridazine, pyrazole, pyridine, substituted urea and phenyl carbamate derivatives containing benzofuran moiety were synthesized via reaction of sodium salt of 5-hydroxy-l-benzofuran-2-ylpropenone or 1-(benzofuran-2-yl)-3-(dimethylamino)prop-2-en-1-one with diazotized heterocyclic amines, hydroximoyl chlorides and active methylene compounds. The structures of all the newly synthesized compounds were confirmed by elemental analyses, spectral data, and alternative synthetic routes, whenever possible.